Women's Patchwork Dresses with Mixed Media Techniques in the Creation of Painting - Johari, Adawiah Rizqi; Tarenaksa, Babat Nufus; Maharoni G, Lalu Aswandi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The purpose of this final project entitled